SOSIALISASI PEMBERIAN MAKANAN BERGIZI PENDAMPING ASI PADA IBU BAYI SEBAGAI INTERVENSI UNTUK MENURUNKAN PREVALENSI STUNTING DI DESA DOREBARA - Astika, Reni; Rachmatullah, Reza; Farid, Muhammad Jailul Qurani; Adhiyasa, I Kadek Wisnu; Fachreza, Muhammad Rafli; Halimatuzzakrah, Halimatuzzakrah; Hidayanti, Silpiya; Rismiyati, Rismiyati; Rachmani, Dyah Fitri; Misbahuddin, Misbahuddin (Jurnal Wicara, 2023)
This article discusses intervention efforts to address stunting in Dorebara Village, Dompu Regency, through the Community Empowerment Real Work Lecture (KKN PMD) program by Universitas Mataram. The program involves the dissemination of information about the risks of stunting and the Practice of Clean and Healthy Living (PHBS), the provision of Complementary Feeding (MPASI) in the form of "Chicken Corn Soup," health surveys of prospective brides (Catin) using the Elsimil application, and knowledge about the implications of early marriage. The results indicate an increased understanding within the community regarding stunting prevention, proper childcare practices, and the importance of appropriate MPASI. In essence, this program offers concrete solutions and holds the potential to reduce the prevalence of stunting in the area.